Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have a text book question to find the principal argument of

$$ z = {i \over -2-2i}. $$

I know formulas where we find using $$ \tan^{-1} {y \over x}$$

but I am kinda stuck here can somebody please help.

share|cite|improve this question

Rewrite as

$$z = -\frac{1+i}{4}$$

Note that $\Re{z} = \Im{z} = -1/4$, so that the argument of $z$ lies in the third quadrant (same sign, both negative). Because the real and imaginary parts are equal,

$$\text{Arg}\,{z} = \frac{-3 \pi}{4}$$

share|cite|improve this answer
yup got that part now to find the Arg(z) what should i do? – Kishan Thobhani Mar 15 '13 at 13:38
@RonGordon, Accroding to you, the principal argument of Arg(a+ia) will be $\frac\pi4$ for $a\ne0$ right? But the principal argument lies $\in( −\pi,\pi]$… – lab bhattacharjee Mar 15 '13 at 14:37
@labbhattacharjee: I see. This is confusing because the principal value of the arctan lies between $-\pi/2$ and $\pi/2$. I think I have had run-ins of this type here before. – Ron Gordon Mar 15 '13 at 14:44
@RonGordon, $Arg(1+i)$ should not be equal to $Arg(-1-i),$ right? – lab bhattacharjee Mar 15 '13 at 14:45
@labbhattacharjee: I am not disagreeing with you. I know that when I want the correct quadrant, I use atan2. I know of "principal value" from the use of Arctan, that's my issue. But if that's the accepted use of the word, so be it. – Ron Gordon Mar 15 '13 at 14:47

$$z=\frac i{-2-2i}=\frac12\frac {-i}{1+i}=\frac12\frac {-i(1-i)}{(1+i)(1-i)}=\left(-\frac14\right)+i\left(-\frac14\right)$$

Using the definition of $\arctan2,$

the principal value of the Argument of $z$ (which lies in $(-\pi,\pi]$) will be $\arctan 1 -\pi=\frac\pi4-\pi=-\frac{3\pi}4$ (as $\frac{\left(-\frac14\right)}{\left(-\frac14\right)}=1$)

Alternatively, using this, $$Arg \left(\frac {z_1z_2\cdots}{w_1w_2\cdots}\right)=\sum Arg(z_i)-\sum Arg(w_i)\pmod {(-\pi,\pi]}$$

$$\text{So, }Arg \left(\frac i{-2-2i}\right)= Arg(i)-Arg(-1)-Arg(1+i)$$ $$=\frac\pi2-\pi-\frac\pi4\pmod {(-\pi,\pi]}=-\frac{3\pi}4$$

share|cite|improve this answer

$z = \cfrac{i}{ -2-2i}=\cfrac{i(-2+2i)}{ (-2-2i)(-2+2i)}=\cfrac{i(-2+2i)}{ (-2-2i)\overline{(-2-2i)}}=\cfrac{i(-2+2i)}{ \left|-2-2i\right|^2}=\cfrac{-2i-2}{ \left|-2-2i\right|^2}=\cfrac{1}{ \left|-2-2i\right|^2}(-2-2i)$

Since $\cfrac{1}{ \left|-2-2i\right|^2}\in \Bbb R_+^*$, the principal argument of $z$ is also the principal argument of $-2-2i$ which you should be able to find.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.